A phase-convertible fast ionic conductor with a monolithic plastic crystalline host. Issue 17 (21st April 2021) - Lee, Seongsoo; Moon, Janghyuk; Bintang, His Muhammad; Shin, Sunghee; Jung, Hun-Gi; Yu, Seung-Ho; Oh, Si Hyoung; Whang, Dongmok; Lim, Hee-Dae
Abstract : We present a fast Mg 2+ -ion conductor with a monolithic plastic crystalline host. Also, conformal contact with a solid electrode can be achieved by using the reversible phase transition of succinonitrile through simple heating and cooling processes. Abstract : Designing a fast ionic conductor has been an essential issue in next-generation batteries based on all-solid-state systems, with specific application targets in large-scale energy storage devices. For this wide range of applications, high levels of ionic conductivity, as well as safety, should be preferentially ensured. However, current solid electrolyte technology is unable to meet the high standards of acceptable conductivity and becomes more problematic in multivalent-ion batteries. Herein, we have proposed a novel phase-convertible ionic conductor based on a monolithic succinonitrile (SN) plastic crystalline material. The unique properties of SN, with high polarity and high rotational degrees of freedom, enable it to dissolve Mg salts and allow for fast transport of cations in the solid phase. For the first time, a high Mg 2+ ion conductivity of 2.8 × 10 −5 S cm −1 was demonstrated at room temperature, and high chemical and thermal stabilities with a wide electrochemically stable window were proven. The monolithic SN structure was able to process simple phase transitions between liquids and solids; therefore, the highly deformable phase-convertible ionic conductor enabled the formation of excellent conformal contact with the electrode. In addition, the origin of the high conductivity was theoretically investigated through density functional theory calculations. We believe that the unique host of monolithic SN is a useful platform with potential applicability for most kinds of cation with fast ion-conducting properties.